THE IMPLEMENTATION ANALYSIS OF THE CONCEPT OF ISLAMIC FAIRNESS IN THE BUSINESS FROM THE PERSPECTIVE OF TRADERS AT AZ-ZAITUN I SHARIA MARKET SURABAYA - Dandi Setiabakti; R. Moh. Qudsi Fauzi (Universitas Airlangga, 2020)
The aim of this research was to describe the implementation of the concept of Islamicfairness in business by traders of the Az-Zaitun I Surabaya Sharia Market. This research uses qualitative approach with descriptive case study strategy. The primary data obtained using purposive sampling through interviews. Participatory observation also conducted to the traders. Secondary data is obtained from textbooks, scientific journals, and online articles that are relevant to this research. Then, triangulation conducted and analyzed to get the conclusion. The result of this study shows that the traders of the Az-Zaitun I Surabaya Sharia Market apply all of fair concept according to the three meanings of fairness, namely equal, proportional, and divine orientation. The conclusion is even though it doesn't have a market supervisor, The Az-Zaitun I Surabaya Sharia Market has applied the three meanings of Islamic fairness, namely equal, proportional, and divine orientation.Keywords: Islamic Fairness, Equal, Proportional, and Divine Orientation.REFFERENCES Al-Qur’an dan Terjemahannya. (2005). Departemen Agama Republik Indonesia, Edisi Baru Cetakan 2005. Jakarta: Pustaka Amani Jakarta.Al-Albani, M. Nashiruddin. (2005). Ringkasan shahih muslim. Cetakan Pertama. Terjemahan Elly Lathifah. Jakarta: Gema Insani Press.Al-‘Asqalani, Al-Hafidzh Ibnu Hajar. (2007). bulughul maram ta’liq dan takhrij: berdasarkan kitab-kitab syaikh muhamad nashiruddin al-albani dan syaikh ahmad syakir. Cetakan Pertama. Terjemahan Zaid Muhammad., dkk. Jakarta: Pustaka as-sunnah.Aziz, Abdul. (2013). Etika bisnis perspektif islam, implementasi etika bisnis islami untuk dunia usaha. Cetakan Pertama. Bandung: CV. ALFABETA.Djamil, Fathurrahman. (2015). Hukum ekonomi Islam: sejarah, teori, dan konsep. Cetakan Kedua. Jakarta: Sinar Grafika.Haritsi, Jaribah bin Ahmad Al. (2006). Fikih ekonomi Umar bin Al-Khattab. Cetakan Pertama. Terjemahan Asmuni Solihan Zamakhsyari. Jakarta: Pustaka Al-kautsar.Jusmaliani, dkk. (2008). Bisnis berbasis syariah. Cetakan Pertama. Jakarta: Bumi Aksara.Karim, Adiwarman A. (2014). Ekonomi mikro Islam. Edisi Kelima Cetakan Keenam. Jakarta: Rajawali Pers.Khadduri, Majid. (1999). Teologi keadilan. CetakanPertama. Terjemahan Zoerni, H. Mochtar dan Kahhar, Joko S. Surabaya: Risalah Gusti.Muslich. (2007). Bisnis syariah perspektif mu’amalah dan manajemen. Cetakan Pertama. Yogyakarta: Unit Penerbitan dan Percetakan Sekolah Tinggi Ilmu Manajemen YKPN.Nawawi, Ismail. (2012). Fikih muamalah klasik dan kontemporer hukum perjanjian, ekonomi, bisnis, dan sosial. Cetakan Pertama. Bogor: Ghalia Indonesia.Pusat Pengkajian dan Pengembangan Ekonomi Islam (P3EI) Universitas Islam Indonesia Yogyakarta. (2012). Ekonomi Islam. Edisi Pertama Cetakan Keempat. Jakarta: Rajawali Pers.Ramdan, Anton. (2013). Etika bisnis dalam Islam. Edisi Pertama Cetakan Pertama. Jakarta: Bee Media Indonesia.Shaukat, Mughees., Rahman, Mohammad Saeed., Luka, Saji. (2017). The nexus between business ethics and economics justice: an Islamic framework. Journal of Economic Development, Management, IT, Finance and Marketing, 9(1), 1-11. (https://search.proquest.com/docview/1861052108?accountid=50637, Diakses 8 Januari 2018).Shihab, M. Quraish. (1998). Wawasan al-qur’an: tafsir maudhu’i atas pelbagai persoalan umat. Cetakan kedelapan. Bandung: Mizan.S, Jai. (2013). Feature: masuk pasar seperti masuk taman. (http://tanahapikata.blogspot.com, diakses tanggal 27 Juni 2018).Sugiyono. 2010. Metode penelitian bisnis (pendekatan kuantitatif, kualitatif, dan R&D). Cetakan ke-15. Bandung: Alfabeta.Suharso dan Retnoningsih, Ana. (2011). Kamus Besar Bahasa Indonesia (KBBI). Edisi Lux. Cetakan keenam. Semarang: Widya Karya.Tarmizi, Erwandi. (2016). Harta haram muamalat kontemporer. –Cet. Ke-12. Bogor: PT Berkat Mulia Insani.